TREATMENT OF ESOPHAGEAL OBSTRUCTION IN HORSES USING AN ALTERNATIVE SURGICAL TECHNIQUE TO ESOPHAGOTOMY - CAJU, F. M.; RIZZO, H.; SILVA, E. S.; ASSIS JUNIOR, E. B.; OLIVEIRA, M. G.; AZEVEDO, N. M. S.; ARAÚJO, S. R. F. (Ars Veterinaria, 2025)
Esophageal obstruction in horses can be associated with factors of primary (food impaction) or secondary (tumors, abscesses) origin. Surgical treatment of primary cases is generally performed by esophagotomy. However, this technique has a high incidence of wound dehiscence, stenosis, and other post-surgical complications. This report aims to describe the surgical treatment, without esophagotomy, of esophageal obstruction caused by a mango pit in a horse. The diagnosis was established based on the association of history, physical examination, nasogastric intubation, radiography, and endoscopy. Due to the impossibility of displacing the foreign body using a nasogastric tube, a surgical procedure was indicated. With the animal in a standing position, sedated and under local anesthesia, the esophageal region was accessed through an incision in the cranial third of the ventrolateral cervical region. Proximal to the obstruction site, 10 mL of 50% propylene glycol was injected into the esophageal lumen, cranial to the foreign body, to promote lubrication. Afterward, successive “milking” movements were performed in a cranial direction on the distal portion of the obstructed segment until the seed reached the oral cavity, from where it was manually removed. Five days after the procedure, the animal died, and necrotizing esophagitis, gastric ulcers, and aspiration pneumonia were observed. The surgical technique used is viable, however the prognosis regarding life and function depends on the duration of the obstruction, the occurrence of aspiration, and the involvement of important organs.